(untitled) (Global Journal of Management and Business Research, 2025)
This study examined the causal impact of zakat compliance on the institutional performance of Yemen’s General Authority for Zakat. It employs a novel integrated theoretical framework that combines the Theory of Planned Behavior, Social Exchange Theory, and Organizational Legitimacy Theory-a comprehensive approach not previously applied in the context of zakat institutions with this level of comprehensiveness. A quantitative research design was adopted, and data were collected from 398 managerial staff members using a validated electronic questionnaire. The relationships among five dimensions of zakat compliancereligiosity, trust, awareness, zakat as a tax deduction, and the administrative and regulatory system-were examined using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that zakat compliance has a substantial effect on institutional performance, explaining 90.8% of its variance (R² = 0.908).